Association of the Stress Hyperglycemia Ratio with Advanced Liver Fibrosis and Mortality in Patients with Metabolic Dysfunction–Associated Steatotic Liver Disease: An Analysis of NHANES - Su, Zhongping; Ling, Tao; Mao, Runming; Yang, Xueming; Wang, Jian; Xu, Yujie (Turkish Journal of Gastroenterology, 2026)
Background/Aims: Changes in blood glucose are correlated with metabolic dysfunction associated steatotic liver disease (MASLD). The stress hyperglycemia ratio (SHR) serves as an innovative biomarker for accurately assessing acute hyperglycemia. This investigation aimed to analyze the correlation of SHR with advanced liver fibrosis and mortality among MASLD patients. Materials and Methods: This retrospective analysis enrolled 8078 individuals with MASLD (fatty liver index ≥60) from the National Health and Nutrition Examination Survey 1999-2018. The outcomes were advanced liver fibrosis (fibrosis 4 index >2.67), all-cause mortality (ACM), and cardiovascular disease–related mortality (CRM), and death information was recorded through December 31, 2019. The SHR was calculated using fasting plasma glucose (FPG) and glycated hemoglobin (HbA1c) according to the following formula: [FPG (mmol/L) / (1.59 × HbA1c (%) - 2.59)]. Results: Among the 8078 patients, advanced liver fibrosis was identified in 243 (2.12%) patients, while ACM and CRM accounted for 1250 (9.12%) and 421 (2.92%) patients, respectively. High SHR demonstrated a correlation with higher risks of advanced liver fibrosis [odds ratio (OR, 95% CI) = 1.87 (1.15-3.04)] and ACM [hazard ratio (HR, 95% CI) = 1.45 (1.11-1.89)]. Low SHR was also related to a higher risk of ACM [HR = 1.34 (1.00-1.78)]. The SHR showed a U-shaped nonlinear relationship with advanced liver fibrosis, ACM, and CRM, and the lowest SHR values were 0.924, 0.924, and 0.945, respectively. Conclusion: The SHR exhibited a U-shaped relationship with the risk of advanced fibrosis and mortality among MASLD patients. Cite this article as: Su Z, Ling T, Mao R, Yang X, Wang J, Xu Y. Association of the stress hyperglycemia ratio with advanced liver fibrosis and mortality in patients with metabolic dysfunction–associated steatotic liver disease: An analysis of NHANES. Turk J Gastroenterol. Published online February 16, 2026. doi: 10.5152/tjg.2026.25707.